IDENTIFICATION AND PURIFICATION OF TOMATO MOSAIC VIRUS (ToMV) AND ANTISERUM PRAPARED BY USING IMMUNIZED CHICKEN EGGS. - Kassim, Nabil A.; Daham, Anaheed Waadallah (Diyala Agricultural Sciences Journal, 2013)
Tomato mosaic virus (ToMV) was diagnosed by using indicator plants. ToMV was purified by differential centrifugation, after filtrate by agarose gel filtration, from tobacco leaves its purity and concentration were 1.3 and 1.3 mg/gm. plant juice respectively , and it was effective in inducing infection on leaves of wild tobacco. The isoelectric point of the virus was 4.4 pH. The antiserum of ToMV was prepared by using immunized chicken eggs, and was tested by agar double diffusion and slide agglutination tests.